2020
DOI: 10.1039/c9ra10014h
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic approach to cascade synthesis of bis(indolyl)methanes in pure water

Abstract: TLIM: lipase from Thermomyces lanuginosus immobilized on particle silica gel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…The decrement in the yield of the reaction at a higher concentration of the enzyme is due to the aggregation of enzyme molecules, which affects the interaction between substrate and enzyme molecule due to the blockage of the active sites of the enzyme. 43 Fu et al have also reported that a higher enzyme loading did not raise the reaction yield. 43 b A set of control reactions was conducted to confirm the role of the developed catalyst (entries 6–8, Table 3 ).…”
Section: Resultsmentioning
confidence: 96%
“…The decrement in the yield of the reaction at a higher concentration of the enzyme is due to the aggregation of enzyme molecules, which affects the interaction between substrate and enzyme molecule due to the blockage of the active sites of the enzyme. 43 Fu et al have also reported that a higher enzyme loading did not raise the reaction yield. 43 b A set of control reactions was conducted to confirm the role of the developed catalyst (entries 6–8, Table 3 ).…”
Section: Resultsmentioning
confidence: 96%
“…Based on the experimental results and relevant studies, 9,47–50 a plausible mechanism of this lipase‐catalyzed hydrazine insertion is illustrated in Scheme 2. First, the carbonyl group of MBH ketone ( 1a ) was reacted spontaneously with phenylhydrazine ( 2a ) to generated the intermediate I via an aza‐Michael addition.…”
Section: Resultsmentioning
confidence: 99%
“…[39] Based on our experimental results and previous studies, a reasonable mechanism for this MCR is proposed in Scheme 3. [40][41][42] First, aldehydes (2) and sulfonamides (3) form 5 via spontaneous nucleophilic addition. Dehydration then generates sulfonamides via reversible reactions.…”
Section: Chemistryselectmentioning
confidence: 99%